Psicanálise e musicalidade(s): sublimação, invocações e laço social - Tavares, Leandro Anselmo Todesqui [UNESP] (2014)
Taking into consideration the constant development necessary for the establishing of Psychoanalysis as a field of knowledge (Freud, Lacan), the thesis presented here aims at a deeper theoretical study on the relations between musicality and the Psyche, as well as a contributing for interdisciplinary studies We approach this theme from different perspectives: an investigative perspective related to creation and sublimation in psychoanalysis; a constructive perspective related to the metapsychology of the musical-sound object. Music is chosen as privileged object of study in its interfaces with psychoanalysis to the extent of opening contributions to the understanding of the subject and its possibilities in the texture of its origins, through social ties and culture. This study constitutes in a proposal for a rapprochement and a dialogue with the field of the arts through the prism of musicality, recovering the inventive insight by Freud and Lacan from the perspective of Involved Psychoanalysis. Music and/or musicality maintain relations with intrinsic psychic events for the constitution of the subject as well as for the link to the other. By means of an updating of the concept of sublimation, the function of contagion is brought into focus highlighting its psychic correlates in its relations with musicality. The study of the invocatory drive revealed relations with time of sublimation and music and/or musicality in regards to the metapsychology presening itself as a poetics of the unspeakable capable of producing destinations (musicantes) at the unheard of the subjects(s). Because of it unique metapsychologival quality – excessively invoking – musicality is characterized as a privileged form transmission from and into the real performing the function of proximity in the register of culture and in the invocation of the social bond itself